Influence of Cu(NO3)2 Activator and Gas Composition on the Thermal Decomposition of Coal and Lignite; Coke and Chemistry; Vol. 63, iss. 3 - Larionov K. B. Kirill Borisovich; Mishakov I. V. Iljya Vladimirovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Lavrinenko S. V. Sergey Viktorovich; Gromov A. A. Aleksandr Aleksandrovich; Vedyagin A. A. Aleksey Anatolievich (2020, 2020)
Title screen